Hydrogeochemical constraints on the genesis, fluid mixing, and heavy metal mobilization of low-temperature geothermal systems in the Mufushan granite batholith, South China - Linxin Li; Zhengqing Wu; Lei Wang; Jian Ou; Jing Pi; Sheng Liu; Lala Wei; Liuqin Huang; Hongchen Jiang; Yanlong Dong (Geothermics, 2026)

Study and application of energy-dissipating yielding support for large deformation in hard rock tunnel subjected to extremely high geostress - Sheng Pi; Mingnian Wang; Xun Luo; Li Yu; Youlin Qin (Tunnelling and Underground Space Technology, 2026)

Unveiling the gut-brain axis: How chronic exposure to arsenic-induced microglial pyroptosis drives Alzheimer's disease-like pathology - Jianyu Qu; Xin Jiang; Ying Ma; Xin Sheng; Changyi Pi; Yuanbin Wang; Qiurong Xu; Rican Li; Peiran Wang; Dongping Qian; Ji Wang; Zili Yi; et al. (Journal of Hazardous Materials, 2026)

Investigating the land hermit crab trade in physical pet shops across three Asian Countries: Implications for conservation management - Chia-Hsuan Hsu; Shi-Sheng Liu; Sin-Tung Choi; Tzu-Pi Chen; Bao-Min Gan; Wei-Ting Chen; Takahiro Kubo (Journal for Nature Conservation, 2026)

The electric double layer governs the spatially-variable thermodynamic equilibrium of gas hydrates in clays - Sheng-Li Li; Yu-Xiang Chen; John J. Carroll; Shu-Hui Jiang; Pi-Bo Su (Chemical Engineering Journal, 2025)

Antinode-centre near-infrared tandem OLEDs enabled by ultrathin emissive layers - Min Song; Zheng Ren; Sheng-Fu Wang; Xiao-Bo Shi; Wei-Zhi Liu; Zi-Qi Feng; Dong-Ying Zhou; Pi-Tai Chou; Liang-Sheng Liao (Chemical Engineering Journal, 2025)

Research Progress in Controlling Root Rot in Sugar Beet - Jing-Hao Li; Sheng-Nan Li; Zhi Pi; Ze-Dong Wu (Sugar Tech, 2025)

Genetic Diversity Analysis of 89 Monogerm Maintainer Lines of Sugar Beet - Jing-Jing Zhao; Lin-Lin Sun; Zhi Pi; Sheng-Nan Li; Ze-Dong Wu (Sugar Tech, 2025)

Critical windows for exposure to chemical composition of ambient particulate matter and human semen quality decline - Lingxi Wang; Qiling Wang; Yunchong Yao; Jiayi Zhou; Xiaoyan Cai; Tingting Dai; Chunying Song; Yushan Li; Fuping Li; Tianqing Meng; Huiqiang Sheng; Pi Guo; et al. (Science of The Total Environment, 2024)

Beneficial effect of residential greenness on sperm quality and the role of air pollution: A multicenter population-based study - Tingting Dai; Wei Li; Lingxi Wang; Jiayi Zhou; Kaixin Zhong; Yunchong Yao; Xiaoyan Cai; Linwei Tian; Haisheng Wu; Ting Xu; Lina Xiao; Haobo Ni; et al. (Science of The Total Environment, 2024)

Feasibility and Acceptability Evaluation of a Digital Therapeutic Program for Improving Cancer Prevention: A Quasi-experimental Pre-post Interventional Pilot Study - Xianwei Zhang; Sheng Zhang; Haiyan Zhang; Ziyou Xiong; Yi Li; Lufeng Li; Xitian Pi; Hongying Liu (Journal of Cancer Education, 2024)

Constructing DNA Fingerprinting and Evaluating Genetic Diversity Among Sugar Beet (Beta vulgaris L.) Varieties Based on Four Molecular Markers - Xue-Mei Liang; Zhi Pi; Ze-Dong Wu; Sheng-Nan Li (Sugar Tech, 2023)

Sperm quality decline associated with gaseous pollutant exposure: Evidence from a large cohort multicenter study - Xiaoyan Cai; Haobo Ni; Qiling Wang; Tingting Dai; Lingxi Wang; Chunying Song; Yushan Li; Fuping Li; Tianqing Meng; Huiqiang Sheng; Lina Xiao; Ting Xu; et al. (Journal of Hazardous Materials, 2023)

Long-term cadmium exposure impairs cognitive function by activating lnc-Gm10532/m6A/FIS1 axis-mediated mitochondrial fission and dysfunction - Ping Deng; Huadong Zhang; Liting Wang; Sheng Jie; Qi Zhao; Fengqiong Chen; Yang Yue; Hui Wang; Li Tian; Jia Xie; Mengyan Chen; Yan Luo; et al. (Science of The Total Environment, 2023)

An Analytical Solution of Transient Wave Generation in the Wave Channel - Cheng-Tsung Chen; Jaw-Fang Lee; Kuei-Ting Lin; Pi-Sheng Hu (Journal of Marine Science and Engineering, 2022)
Transient characteristics of wave generation in the wave channel can provide unique and important information in contrast to the steady and periodic motion of propagation waves. In this paper, a new analytical solution is proposed for a transient wavemaker problem in the wave channel. The mathematical model of the wavemaker problem is established based on the linear potential wave theory, and a new analytical solution for the corresponding initial and boundary-value problem is presented. The present solution methodology is motivated and developed from old methods shown in literature. The present solution can be mathematically reformulated and shown to be identical to the previous solution using different solution methodology. The present analytical solution is further compared with numerical results and experiments to validate the mathematical model. The present solution is used to calculate the steady state generated wave forms that compare very well with the steady wave theory both in wave length and wave period. The present solution is also used to study unsteady characteristics of wave heights and wave lengths of the leading waves. The present analytical solution methodology can provide an easier approach to obtain the analytical solution for transient wave generation problem in the wave channel.

A comparison of atmospheric geochemistry through lichens from volcanic and non-volcanic areas, north Taiwan - Le-Qi Lin; Hsueh-Yu Lu; Ju-Lien Pi; Tai-Sheng Liou; Wen-Fu Chen; Pei-Shan Hsieh (Journal of Earth System Science, 2021)

Three-dimensional Spheroid Culture Enhances Multipotent Differentiation and Stemness Capacities of Human Dental Pulp‐derived Mesenchymal Stem Cells by Modulating MAPK and NF-kB Signaling Pathways - Ya-Hui Chan; Yu-Chieh Lee; Chia-Yi Hung; Pi-Ju Yang; Pin-Chuang Lai; Sheng-Wei Feng (Stem Cell Reviews and Reports, 2021)

Shallow gas hydrates off southwest Taiwan and their mechanisms - Yin-Sheng Huang; Shu-Kun Hsu; Chih-Chieh Su; Andrew Tien-Shun Lin; Pai-Sen Yu; Nathalie Babonneau; Gueorgui Ratzov; Serge Lallemand; Pi-Chuen Huang; Shiao-Shan Lin; Jing-Yi Lin; Kuo-Yen Wei; et al. (Marine Geophysical Research, 2021)
We have collected two shallow gas hydrate samples at two sites having different geological settings off southwest Taiwan during the cruise MD214 in 2018. The first core site, MD18-3542, is on the South Yuan-An East Ridge at ~ 1200 m water deep, where a structural unconformity covered by fine-silt sediments appears at ~ 5.5 m below the seafloor. The second core site, MD18-3543, is close to the Good-Weather Ridge at ~ 1100 m water deep, where a gas-related pockmark structure and authigenic carbonates are present at shallow strata with fine-silt sediments near the seafloor. Sediment properties of core MD18-3542 are distinctively different above and below the layer corresponding to the unconformity. Both cores show obvious gaps or voids in the lower core halves. The core features could be linked to the dissociated methane upward migrating from deep strata. Core site settings with upwelling methane would favor the formation of shallow gas hydrates. At site MD18-3542, the shallow hydrate could be formed due to high concentration methane kept beneath the unconformity covered by fine-silt sediments. At site MD18-3543, the shallow hydrate could be formed due to an extremely high flux of upwelling methane trapped either beneath the authigenic carbonates or fine-silt sediments.

Chinese public participation monitoring and warning system for geological hazards - Sheng-nan Wu; Yu Lei; Peng Cui; Rong Chen; Pi-hua Yin (Journal of Mountain Science, 2020)

Identification and characterization of two morphologically distinct stem cell subpopulations from human urine samples - An-Jing Chen; Jin-Kui Pi; Jun-Gen Hu; Yi-Zhou Huang; Hong-Wei Gao; Sheng-Fu Li; Jesse Li-Ling; Hui-Qi Xie (Science China Life Sciences, 2020)

Sodium Metabisulfite: Effects on Ionic Currents and Excitotoxicity - Ming-Chi Lai; Te-Yu Hung; Kao-Min Lin; Pi-Shan Sung; Shyh-Jong Wu; Chih-Sheng Yang; Yi-Jen Wu; Jing-Jane Tsai; Sheng-Nan Wu; Chin-Wei Huang (Neurotoxicity Research, 2018)

Discovery of a novel multifunctional carbazole–aminoquinoline dimer for Alzheimer's disease: copper selective chelation, anti-amyloid aggregation, and neuroprotection - Xiao Zhang; Ying Wang; Sheng-nan Wang; Qiu-he Chen; Ya-lin Tu; Xiao-hong Yang; Jing-kao Chen; Jin-wu Yan; Rong-biao Pi; Yan Wang (Medicinal Chemistry Research, 2018)

Response of Selenium and Selenogenome in Immune Tissues to LPS-Induced Inflammatory Reactions in Pigs - Lv-Hui Sun; Ding-An Pi; Ling Zhao; Xiu-Ying Wang; Luo-Yi Zhu; De-Sheng Qi; Yu-Lan Liu (Biological Trace Element Research, 2017)

Synthesis and evaluation of multifunctional ferulic and caffeic acid dimers for Alzheimer’s disease - Xi-xin He; Xiao-hong Yang; Rui-ying Ou; Ying Ouyang; Sheng-nan Wang; Zi-wei Chen; Shi-jun Wen; Rong-biao Pi (Natural Product Research, 2017)

Distribution and abundance of octocoral (Octocorallia, alcyonacea) communities at three Southern Islands of Singapore - Jason Zhi Sheng Seah; Nicholas Wei Liang Yap; Lik Tong Tan; Beverly Pi Lee Goh (Ocean Science Journal, 2015)

Zinc attenuation of GDP binding to brown adipocytes mitochondria in genetically obese (ob/ob) mice - Ming-Der Chen; Pi-Yao Lin; Piin-Sheng Chen; Vie Cheng; Wen-Han Lin (Biological Trace Element Research, 1997)